Counting the Homeless in Greece - Arapoglou, Vassilis; Dimoulas, Constantine; Richardson, Clive (Κοινωνική Πολιτική, 2021)
We present the main findings from pilot research on the homeless population in six municipal areas in Greece in 2018. The project employed the “point-in–time” technique, combining counting by observation with interviewing where possible. The procedure succeeded in engaging local communities and NGOs in enumerating the homeless population. A large part of the housing needs of the homeless remains unmet, especially in the major metropolitan centres, despite increased provision of emergency shelters and services since 2012. Younger ages face alarming difficulty in accessing housing support. Financial hardship and unemployment contribute separately and interactively with other stressors to increased homelessness.